1998
DOI: 10.1099/00221287-144-9-2545
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a unique benzothiophene-desulphurizing bacterium, Gordona sp. strain 213E (NCIMB 40816), and characterization of the desulphurization pathway

Abstract: Gordona sp. strain 213E (NCIMB 40816) grew in pure culture in a mineral salts medium containing fructose as a source of carbon and energy, and benzothiophene (BTH) as the sole source of sulphur. During growth a phenolic compound accumulated, as indicated by the production of a blue colour on addition of Gibb's reagent. Therefore this pathway is analogous to the dibenzothiophene (DBT) desulphurization pathway of Rhodococcus sp. strain IGTS8, in which 2-hydroxybiphenyl accumulates during growth with DBT as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 33 publications
5
71
0
Order By: Relevance
“…However, no bacterial strain has been found that is able to grow on benzothiophenes as the sole carbon source, and all reported biotransformations of benzothiophenes are based on cometabolism. Attacks on the thiophene ring of benzothiophenes lead to the formation of sulfoxides and sulfones, or to ring opening and the formation of 2-mercaptomandelaldehyde and 2-mercaptophenylglyoxalate (Saftić et al, 1992;Eaton & Nitterauer, 1994;Gilbert et al, 1998). Interestingly, it has been reported that BTO is trapped as a Diels-Alder-type disulfoxide cycloadduct, which yields (Kropp et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no bacterial strain has been found that is able to grow on benzothiophenes as the sole carbon source, and all reported biotransformations of benzothiophenes are based on cometabolism. Attacks on the thiophene ring of benzothiophenes lead to the formation of sulfoxides and sulfones, or to ring opening and the formation of 2-mercaptomandelaldehyde and 2-mercaptophenylglyoxalate (Saftić et al, 1992;Eaton & Nitterauer, 1994;Gilbert et al, 1998). Interestingly, it has been reported that BTO is trapped as a Diels-Alder-type disulfoxide cycloadduct, which yields (Kropp et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…Six metabolites of BT were detected by GC-MS: BTO 2 and 2-mercaptobenzoic acid were identified by comparison of their retention times and mass spectra with those of authentic compounds; 2-hydroxybenzothiophene, 3-hydroxybenzothiophene, benzothiophene-2,3-dione and BTO were identified by comparison of their mass spectra with published data (Saftić et al, 1992;Eaton & Nitterauer, 1994;Kropp et al, 1994b;Gilbert et al, 1998). These results indicate that strain XLDN2-5 is able to catalyse lateral dioxygenation and S oxidation on the thiophene ring of BT.…”
Section: Microbial Transformation Of Benzothiophenesmentioning
confidence: 99%
“…However, no bacterial strain has been found to grow on benzothiophenes as the sole carbon source, and all reported biotransformations of benzothiophenes are based on cometabolism. Attacks on the thiophene ring of benzothiophenes lead to the formation of sulfoxides and sulfones, or to ring opening and the formation of 2-mercaptomandelaldehyde and 2-mercaptophenylglyoxalate [158][159][160]. Catabolism of dibenzothiophene is catalyzed by distinct enzymes in two pathways (Scheme 7).…”
Section: Alicyclic Hydrocarbonsmentioning
confidence: 99%
“…The following strains were used for comparison: R. erythropolis IGTS8 (ATCC 53968) and R. erythropolis X309 (ATCC 55309). A minimal salt medium (MSM) was used for the isolation and cultivation of DBTdesulfurizing strains [18]. DBT and 4,6-dimethylDBT (4,6-DMDBT) were dissolved in hexane (50 mM) and added to the sterilized MSM.…”
Section: Isolation and Identification Of Strainsmentioning
confidence: 99%